Good governance – a discussion from the perspective of new institutional economics, new political economy and social capital theory - Łopaciuk-Gonczaryk, Beata; Fałkowski, Jan (Journal of Public Governance, 2013)
The article discusses the concept of ‘good governance’, its weaknesses and limitations. It also tries to indicate those areas that might be of importance when making the assessment of the quality of governance. The ideas presented here are based on argumentation taken from new institutional economics, new political economy and social capital theory.